UJI KONSENTRASI PENGHAMBATAN MINIMAL, RESISTENSI DAN PENGGUANAAN ANTIBIOTIK UNTUK MENANGGULANGI PENYAKIT MOTIL AEROMONAS SEPTISEMIA (MAS) PADA LELE DUMBO (Clarias gariepinus) - Kamiso H. N.; Triyanto Triyanto; Sri Hartati (Jurnal Perikanan Universitas Gadjah Mada, 1996)
Five isolates of A. hydrophila were used for MIC, and resistency test to rifampicin, kanamycin, chloramphenicol, erythromycin and oxytetracyclin by dilution method with TSB medium. The results indicated that the bacteria had various degree of sensitivity to these antibiotics. Resistency of bacteria isolates increase 1.3 to 6.2 times after they were passaged three times to MIC of the drugs or antibiotics by dilution method. Other test was kanamycin medication conducted by i.p. injection, immersion, and oral methods. The result showed that all kanamycin medication methods were effective to decrease mortality rate caused by A. hydrophilia infection. Oral medication method was the most effective compare to other methods because this method could minimize stress during handling. However, oral medication took much longer time (15 days) than immersion and injection methods (few minutes).